Lectotipificaciones y novedad taxonómica en Spigelia (Loganiaceae) para la flora del Cono Sur - Zanotti, Christian Alejandro (2021)
In the framework of the taxonomic treatment of the family Loganiaceae for the Argentinean Flora, it was necessary to lectotypify 12 names described for the genus Spigelia. On the other hand, Spigelia beccabungoides, cited as endemic to the Flora of Paraguay is synonymized under Justicia comata (Acanthaceae).